2008
DOI: 10.1002/jmv.21262
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus seropositivity in a South African Cohort of HIV co‐infected, ARV naïve patients is associated with renal insufficiency and increased mortality

Abstract: HIV is known to affect the epidemiology, transmission, pathogenesis and natural history of HCV infection whilst studies on the effects of HCV on HIV have shown conflicting results and are confounded by the influence of intravenous drug use and antiretroviral therapy. This study was conducted in KwaZulu-Natal Province in South Africa where HIV is predominantly a sexually transmitted infection. Intravenous drug use is rare in this region and the study population was naïve to antiretroviral therapy. For this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 37 publications
0
16
2
Order By: Relevance
“…This figure is much lower than the figure obtained in our study (15.0%) (Figure 1). Our figure is also higher than what was obtained in similar studies in Kenya, East Africa (10.0%), Senegal, West Africa (1.6%) and South Africa (13.4%) [36][37][38] but lower than that of another Eastern Africa state, Tanzania (18.1%) 39 . The difference in prevalence could be due to differences in social behaviour of the individuals involved in this study and population size of the individual countries 40 …”
Section: Discussioncontrasting
confidence: 82%
“…This figure is much lower than the figure obtained in our study (15.0%) (Figure 1). Our figure is also higher than what was obtained in similar studies in Kenya, East Africa (10.0%), Senegal, West Africa (1.6%) and South Africa (13.4%) [36][37][38] but lower than that of another Eastern Africa state, Tanzania (18.1%) 39 . The difference in prevalence could be due to differences in social behaviour of the individuals involved in this study and population size of the individual countries 40 …”
Section: Discussioncontrasting
confidence: 82%
“…Historically, HIV co-infection causes poorer outcomes in HCV positive patients, with higher rates of chronic HCV infection, cirrhosis, carcinoma and a poorer response to interferon therapy compared with non-HIV infected patients [23][24][25][26]. HCV recurs universally post-transplant and is associated with rapid progress of cirrhosis [27].…”
Section: Discussionmentioning
confidence: 99%
“…There is also a higher incidence of hepatocellular carcinoma in the co-infected population [34,35]. In a demographic population in Africa with little or no intravenous drug abuse, the prevalence of co-infection with hepatitis C was higher in the HIV-positive versus HIV-negative population, suggesting that HIV infection may mute the host response to hepatitis C [36]. In fact, one study found a decrease in IFN-γ production by hepatitis C-infected CD4+ T-lymphocytes [37].…”
Section: Hepatic Diseasementioning
confidence: 94%